2013
DOI: 10.1089/ten.tea.2012.0745
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor, Brain-Derived Neurotrophic Factor, Neurotrophin-3 and Glial-Derived Neurotrophic Factor Enhance Angiogenesis in a Tissue-EngineeredIn VitroModel

Abstract: Skin is a major source of secretion of the neurotrophic factors nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and glial-derived neurotrophic factor (GDNF) controlling cutaneous sensory innervation. Beside their neuronal contribution, we hypothesized that neurotrophic factors also modulate the cutaneous microvascular network. First, we showed that NGF, BDNF, NT-3, and GDNF were all expressed in the epidermis, while only NGF and NT-3 were expressed by cultured fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 40 publications
1
33
0
2
Order By: Relevance
“…Previous studies showed that Trk receptors play a key role in mediating the mitogenic and angiogenic response of neurotrophins including NGF and BDNF [17, 25, 26]. Our previous work demonstrated significant upregulation of p75 NTR receptor expression in clinical and experimental diabetes [11, 27].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies showed that Trk receptors play a key role in mediating the mitogenic and angiogenic response of neurotrophins including NGF and BDNF [17, 25, 26]. Our previous work demonstrated significant upregulation of p75 NTR receptor expression in clinical and experimental diabetes [11, 27].…”
Section: Resultsmentioning
confidence: 89%
“…NGF activates two different receptors including the high affinity tropomyosin-related receptor A (TrkA), which is a tyrosine kinase, and the low affinity p75 NTR neurotrophin receptors (p75 NTR ) [16]. Previous studies demonstrated that the angiogenic response of NGF was mediated via activation of TrkA [15, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…40 Our results also correlate with recent findings of a GNDF role in skin de novo blood vessel formation, also supporting signaling interactions between the neural and vascular systems. 41 Thus, NGF and GDNF, having similar effects on perfusion recovery of the ischemic limbs, may act via different signaling cascades in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…They also induce ECM stiffening following direct proteins cross-linking [53]. In addition, most of these processes are interconnected, sensory nerves enhancing keratinocyte proliferation and angiogenesis through neuropeptides release, while keratinocytes support the nerve network maintenance by neurotrophic factors secretion, which are also angiogenic [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that CML formation may decrease over time, probably because of a natural protein turnover, necessitating a continuous glycation to maintain AGE expression. To complete the model, we incorporated endothelial cells to build a capillary-like network as previously described [46,54], enabling the analysis of the impact of glycation on angiogenesis. Sensory neurons obtained from mice embryos were finally incorporated in the model to form a sensory nerve network as previously shown [40].…”
Section: Discussionmentioning
confidence: 99%